2010
DOI: 10.1158/0008-5472.can-09-4362
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Sustained Release Microparticles of Curcumin: A New Concept for Cancer Chemoprevention

Abstract: Poor oral bioavailability limits the use of curcumin and other dietary polyphenols in the prevention and treatment of cancer. Minimally invasive strategies that can provide effective and sustained tissue concentrations of these agents will be highly valuable tools in the fight against cancer. The objective of this study was to investigate the use of an injectable sustained release microparticle formulation of curcumin as a novel approach to breast cancer chemoprevention. A biodegradable and biocompatible polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 52 publications
6
85
0
3
Order By: Relevance
“…Although the efficacy of curcumin is currently under investigation in several clinical trials, its usage is limited by its poor bioavailability, which is due to very rapid renal excretion and hepatic degradation (Shehzad et al 2010). More stable curcumin derivatives or curcumin-releasing microparticles, which have successfully been applied in recent studies (Thomas et al 2008, Shahani et al 2010, may overcome this problem in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy of curcumin is currently under investigation in several clinical trials, its usage is limited by its poor bioavailability, which is due to very rapid renal excretion and hepatic degradation (Shehzad et al 2010). More stable curcumin derivatives or curcumin-releasing microparticles, which have successfully been applied in recent studies (Thomas et al 2008, Shahani et al 2010, may overcome this problem in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relative expression of MMP-9 in tumors from the curcumin PLGA-microparticle treated group was decreased 57% compared to control, while Ki-67 and cyclin D1 were decreased by 45% and 52%, respectively. There was also a 2.5-fold increase in the number of apoptotic cells compared to blank PLGA-microparticle treatment (Shahani et al, 2010). Since repeated systemic dosing of curcumin had no effect on tumor cell proliferation, apoptosis, or the relative cyclin D1 expression, the study concluded that sustained release microparticles of curcumin are more effective than repeated systemic injections of curcumin for breast cancer chemoprevention.…”
Section: Novel Drug Delivery Of Natural Compoundsmentioning
confidence: 87%
“…Specifically, the curcumin PLGA-microparticles treated group showed smaller and less well developed CD31 positive microvessels compared to curcumin alone. Furthermore, treatment with curcumin PLGA-microparticles decreased the relative VEGF expression in tumors by 78%, compared with control (Shahani et al, 2010). Additionally, the relative expression of MMP-9 in tumors from the curcumin PLGA-microparticle treated group was decreased 57% compared to control, while Ki-67 and cyclin D1 were decreased by 45% and 52%, respectively.…”
Section: Novel Drug Delivery Of Natural Compoundsmentioning
confidence: 89%
See 2 more Smart Citations